Propriedades químicas e físicas de um latossolo argiloso afetadas por diferentes tipos e formas de aplicação de calcário - Parize, Guilherme Luiz (2012)
This study was performed for the purpose of evaluating the chemical and physical properties of soil affected by different forms of application of dolomitic and calcitic lime, as well as evaluate their effect on plant yield. An experiment in respect to clayey Latossolo Vermelho distroférrico (Rhodic Hapludox [Oxisol]) was evaluated five years after installation. The following soil attributes were measured: physical attributes (cone index, bulk density and aggregation indexes); chemical attributes (pH, exchangeable cations, H+Al and cation exchange capacity) and plant attributes (soybean root system morphology and crop yields). Five years after surface lime applications (or since 2004), the soil has maintained low acidity, mainly in the 0-5 cm layer, while with incorporation, effects were observed up to a 20 cm depth. There was no response in plant yield to any treatment; however, the soybean root system was deeper (arriving at a depth of 40 cm) under the treatments where the lime was incorporated. With surface liming, root growth was limited to a 10 cm depth. From this study, it may be concluded that five years after application of the treatments, the effect of different forms of lime and their combination on the parameters studied is marginal; the form of lime application is fundamental to root growth of the soybeans, with the chemical/acidity factor being the main mechanism impeding deep root growth